Eksistensi Muatan Lokal Basa Sunda pada Jenjang Pendidikan Anak Usia Dini - Nurapriani, Reni; Darmawan, Deni; Rusman, Rusman (Jurusan PIAUD UIN Siber Syekh Nurjati Cirebon, 2024)
Muatan Lokal is a subject matter that must be carried out at the PAUD level. Muatan Lokal aims to accommodate the potential, excellence and characteristics of each region. One of the Muatan Lokal areas in West Java is Sundanese Muatan Lokal. The results of preliminary studies show that it is still rare for PAUD to organize Muatan Lokal learning in their respective schools. The purpose of this study was to determine the implementation of the Muatan Lokal curriculum at the PAUD level. This research design used a mix method design with an explanatory type. Quantitative data were collected using survey techniques, while qualitative data were collected using interviews. The data source of this quantitative research is teachers at the PAUD level as many as 70 respondents, the qualitative data source consists of teachers at TK Angkasa and TK Islam Nurul Huda Ciamis. Quantitative data analysis using descriptive analysis, qualitative data analyzed by data reduction, data display and verification. The results showed that the Muatan Lokal curriculum at the PAUD level was not fully implemented properly. As many as 31.43 respondents did not have Muatan Lokal curriculum documents, as many as 60% of respondents did not have Muatan Lokal lesson plans. A total of 65.71 respondents did not have Muatan Lokal teaching materials or reference documents. The implementation time of Muatan Lokal learning has not been scheduled systematically. Sundanese is not always used as the language of instruction in Muatan Lokal learning